1975
DOI: 10.1515/cclm.1975.13.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-Stoffwechseluntersuchungen bei unbehandelten Phenylketonurikern

Abstract: Studies on tryptophan metabolism in untreated phenylketonuric patientsThe products of the oxidative degradation of tryptophan via the kynurenine pathway were quantitatively determined in the urine of ten untreated patients with phenylketonuria, aged 4-35 years. All the patients were severely mentally retarded. The results of the analysis suggest a division of the patients into two groups, A and B.-The patients of group A showed a basal urinary excretion of kynurehine, kynurenic acid, 3-hydroxykynurenine and xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A, (2-sulfoindole)-3-acetic acid(14); B, 2,3-dioxindole-3-acetic acid (15); C, 2-(3-indolylmethyl)-indole-3-acetic acid(16).…”
mentioning
confidence: 99%
“…A, (2-sulfoindole)-3-acetic acid(14); B, 2,3-dioxindole-3-acetic acid (15); C, 2-(3-indolylmethyl)-indole-3-acetic acid(16).…”
mentioning
confidence: 99%
“…However, other studies suggest that this substance is produced only in aerobic conditions and the largely anaerobic gut environment would inhibit the production of this substance (Bowden et al, 1976). A study in 10 untreated patients with phenylketonuria showed that 2-aminoacetophenone was excreted as a product of the kynurenine breakdown pathway following tryptophan loading but not following normal dietary intake of tryptophan (Kochen et al, 1975).…”
Section: Candidate Substancementioning
confidence: 99%
“…1) There is no standard method for the determination of xanthurenic acid; some workers use colorimetry (1,7,10), others an array of Chromatographie methods (3,11) or spectrofluorimetry (6).…”
Section: Introductionmentioning
confidence: 99%
“…2) Some authors have administered L-tiyptophan in a mg/kg body-weight dose (5,6,11) and others in a fixed dose (3,4,7,8,9). Even within each of these administrat ion modes the dose used by different authors was not identical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation